Ivabradine, the hyperpolarization-activated cyclic nucleotide-gated channel blocker, elicits relaxation of the human corpus cavernosum: a potential option for erectile dysfunction treatment. (9th April 2021) - Gur, Serap; Alzweri, Laith; Yilmaz-Oral, Didem; Kaya-Sezginer, Ecem; Abdel-Mageed, Asim B.; Sikka, Suresh C.; Hellstrom, Wayne J. G.
Abstract: Objective: To evaluate the effect of the I f channel inhibitor, ivabradine on human corpus cavernosum (HCC) smooth muscle tone. Methods: HCC samples were obtained from erectile dysfunction(ED) patients ( n  = 12) undergoing penile prosthesis surgery. Concentration–response curves for ivabradine were exposed to various inhibitory and stimulatory agents. The relaxant and contractile responses to electrical field stimulation (EFS, 10 Hz and 80 Hz) were examined in the presence or absence of ivabradine (10 μM). HCN3 and HCN4 channel expression and localization were determined by Western blot and immunohistochemical analyses of HCC tissues. Results: Increasing ivabradine concentrations dependently reduced the maximal contractile responses of isolated HCC strips induced by KCl (59.5 ± 2.5%) and phenylephrine (84.0 ± 9.8%), which was not affected by nitric oxide synthase and soluble guanylyl cyclase inhibitors after phenylephrine-induced contraction. Nifedipine and tetraethylammonium inhibited the maximum relaxation to ivabradine by 75% and 39.3%, respectively. Fasudil and sildenafil increased the relaxation response to ivabradine without altering the maximum response. Pre-incubation with ivabradine significantly increased relaxant responses to EFS ( p  < 0.01) and reduced the contractile tension evoked by EFS (72.3%) ( p  < 0.001). Ivabradine incubation did not affect the expression and localization of HCN3 and HCN4 channels in the HCC smooth muscle cells. Conclusions: Ivabradine exhibits a relaxant effect on HCC tissues, which is likely to be attributed to the blocking of L-type Ca 2+ channels and the opening of K + channels, independent of changes in the activation of the nitric oxide/cyclic guanosine monophosphate system. Inhibition of HCN channels localized in cavernosal smooth muscle cells may offer pharmacological benefits for patients with cardiovascular risk factors.